Yagi Antenna With Three Reflector Elements to Amplify 4G Signal In Suburban Areas - Rianto, Rianto; Nawi, Nasrul; malkis, lince (Politeknik Negeri Padang, 2024)
As the number of cell phone users increases and the high cost of 4G network infrastructure, the investment needed to build 4G infrastructure is Rp. 278 trillion, so that many suburban cell phone users (suburban areas) get 4G access with poor network quality. So it requires a repeater as an effective solution with a small capital to increase the coverage area in weak signal areas. Yagi antenna is an antenna suitable for long-distance communication with three reflector elements to strengthen 4G signals in suburban areas at a frequency of 1710-1880 MHz. The material for making the antenna consists of aluminum pipe as a reflector element and a director element with a diameter of 8.4 mm and wire as a driven element with a diameter of 4 mm. In the manufacture there is the addition of a balun supply and three reflector elements which can improve the performance of the parameters of the yagi antenna. Yagi antenna testing is carried out in two ways, namely the Anechoic Chamber room and the Telecommunication Electronics Lab. In this test, the transmitter uses a dipole antenna. and for the transmission cable, use a high school connector cable to operate the Anechoic Chamberm device designated by a female student who has been trained in measurements using the Network Analyzer software. From the results of manual measurements and the Network Analyzer, the results of a unidirectional radiation pattern are obtained, the maximum power level is -23.24 dBm, the frequency resonance 1809 MHz, Bandwidth 52 MHz, HPBW 〖25〗^0, FBR 12.97 dB, Gain 8.572 dB, VSWR 1.09, and Return loss -26.6 dB design using MMANA-GAL software simulation shows that the antenna works at frequency 1,800 MHz, antenna impedance 42.84 + j2,906 Ω, VSWR 1.18, Gain 20.66 dB, and FBR 23.77 dB and has a unidirectional radiation pattern